STRATEGI PEMASARAN SMARTPHONE PT VIVO LAMPUNG INDONESIA - Farah Alhamid (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
PT Vivo Lampung Indonesia is one of the distributors Vivo smartphone in Lampung, targeting local industrial market as a potential market targets. The analysis method used in this research is analysis of IFAS and EFAS matrix, IE matrix, and SWOT matrix. Based on the results of research and data analysis conducted it can be seen that the SWOT matrix analysis resulted in some alternative strategies, among others, to maintain and improve product quality as well as extensive distribution network to increase customer satisfaction and loyalty, improve technology and communication development on smartphone, establish cooperation with potential distributor agent to increase market share , increase the number of smartphone production in accordance with consumer demand, develop a broad market share to enhance consumer brand image, develop product innovation with appropriate selling value, increase consumer confidence in Vivo brand, develop the competitive strategy, also improve and develop maintain the undertaken promotional strategy. Keywords: smartphone, marketing strategy, SWOT